PENGEMBANGAN LKPD BERBASIS KARAKTER MELALUI PENDEKATAN VCT PADA MATERI SILA-SILA PANCASILA KELAS III SEKOLAH DASAR - Chelsy Aimy Palber; Lukman Hakim; Ali Fakhrudin (JS (JURNAL SEKOLAH), 2021)
Abstract :Development Of Character Based LKPD Through VCT Approach To The Principles Of Pancasila Materials Class III Elementary School. This development research aims to: Knowing the procedure, validity, practicality (LKPD) based on character through the VCT approach on the material of the Pancasila Precepts for Grade III Elementary School. The method used in this research is R&D with the ADDIE model. This research was conducted at SD Negeri 74 Palembang. Based on the results of the study, it showed that the assessment by material expert 1 scored 86%, material expert 2 scored 92% ", material expert 3 got a score of 95% with the "Very Valid" category. Media expert 1 is 86%, media expert 2 gets a score of 100%, media expert 3 gets a score of 94% in the "Very Valid" category. The results of the assessment of linguists 1 score 100%, the results of the assessment of linguists 2 score 100%, linguists 3 get a score of 94% in the "Very Valid" category. The results of student responses get an average score of 95.7% and the results of teacher responses get 88.5% results in the "Very Practical" category.Keyword :LKPD, VCT Approach, PancasilaAbstrak :Pengembangan LKPD Berbasis Karakter Melalui Pendekatan VCT Pada Materi Sila-Sila Pancasila Kelas III Sekolah Dasar. Penelitian pengembangan ini bertujuan untu : Mengetahui prosedur, kevalidan, kepraktisan (LKPD) berbasis karakter melalui Pendekatan VCT pada materi Sila-sila Pancasila kelas III Sekolah Dasar. Metode yang digunakan pada penelitian ini adalah R&D dengan model ADDIE. Penelitian ini dilakukan di SD Negeri 74 Palembang. Berdasarkan hasil penelitian menunjukan bahwa penilaian oleh ahli materi 1 skor 86%, ahli materi 2 skor 92%” , ahli materi 3 mendapatkan skor 95% dengan kategori “Sangat Valid”. Ahli media 1 yaitu 86%, ahli media 2 mendapatkan skor 100% , ahli media 3 mendapatkan skor 94% dengan kategori “Sangat Valid”. Hasil penilaian ahli bahasa 1 skor 100%, hasil penilaian ahli bahasa 2 skor 100%, ahli bahasa 3 mendapatkan skor 94% dengan kategori “Sangat Valid”. Hasil respon peserta didik mendapatkan skor rata-rata 95,7% dan hasil respon guru mendapatkan hasil 88,5% dengan kategori “Sangat Praktis”.Kata Kunci :LKPD, Pendekatan VCT, Pancasila